Gender differences in dispensed analgesics in Sweden during 2006–2015 – an observational, nationwide, whole-population study - Bäckryd E (Dove Medical Press, 2018)
Emmanuel Bäckryd Pain and Rehabilitation Centre, Department of Medical and Health Sciences, Linköping University, Linköping, Sweden Introduction: A potentially illuminating way of looking at gender differences in health and disease is to study differences in drug utilization. The aim of this study was to describe gender differences in dispensed analgesics (including nonsteroidal anti-inflammatory drugs [NSAIDs]) in Sweden during 2006–2015. Materials and Methods: The Swedish Board of Health and Welfare holds an open, Anatomical Therapeutic Chemical (ATC)–based statistical database containing aggregated data on all dispensed prescription drugs in Swedish pharmacies since 2006. The database is searchable according to sex, age (5-year intervals), and Swedish regions. Results: Nationwide, whole-population information was retrieved for all ATC codes at the second level for individuals ≥20 years of age, focusing on sex-related differences. More in-depth analyses were made for analgesics, including NSAIDs. Descriptive statistics were used. Gender differences in drug prescription are pervasive in Sweden; the yearly prevalence in 2015 was higher in women for 72 out of 84 ATC groups (not adjusted for age). Analgesics, including NSAIDs, were more commonly used by women in all age groups. Gender differences were sustained over time (2006–2015) and were particularly striking for triptans. For both men and women, the yearly prevalence of opioids was stable during 2006–2015, whereas it increased for paracetamol and decreased for NSAIDs. The increase in paracetamol prescription was most noticeable for young females, and the decrease in NSAID prescription was largest in older patients (irrespective of sex). Conclusion: Gender differences in the use of analgesics probably mirror the higher prevalence of chronic pain in women. Keywords: drugs, medicines, opioids, sex, nonsteroidal anti-inflammatory drugs, NSAIDs, paracetamol, acetaminophen, triptans